Self-repairing UHPC concrete and preparation method thereof

By introducing hydrophilic modified heat shrink fiber mesh and electromagnetic induction self-repair microcapsules into UHPC concrete, the problem of concrete being difficult to cope with crack expansion in complex environments in the prior art is solved, and high strength, excellent durability and self-repair are achieved. Synergistic effect of repair ability.

CN119390412AActive Publication Date: 2025-02-07WUHAN UNIV OF TECH

Patent Information

Application Number
CN202411520943.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-07
Estimated Expiration
2044-10-29

AI Technical Summary

Technical Problem

Existing ultra-high performance concrete is difficult to effectively deal with crack expansion in complex environments, fiber mesh may experience fatigue damage during long-term use, the thermal shrink fiber modification effect is limited, the release process of microcapsule self-repair technology is uncontrollable, and concrete cannot be fully and effectively solved. Structure strength, durability and self-healing problems.

Method used

The hydrophilic modified heat shrink fiber web and electromagnetic induction self-healing microcapsules are introduced into the UHPC concrete matrix. The braided mesh formed by hydrophilic modified polypropylene fiber and nylon fiber provide high strength and toughness and durability, and electromagnetic induction self-healing micro The capsule controllable release of the repair agent is combined with the contraction response of the heat-shrinkable fiber mesh to achieve synergistic repair.

Benefits of technology

It realizes the high strength and toughness and excellent durability of UHPC concrete, and has self-repairing capabilities, and the remediation agent release is controllable, improving the overall performance and applicability of concrete.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses self-repairing UHPC (Ultra High Performance Concrete). The self-repairing UHPC comprises a UHPC matrix, magnetic induction microcapsules and a hydrophilic modified heat-shrinkable fiber net, wherein the magnetic induction microcapsules and the hydrophilic modified heat-shrinkable fiber net are distributed in the UHPC matrix; wherein the magnetic induction self-repairing microcapsule comprises a core material and a wall material, the core material adopts isophorone diisocyanate, and the wall material comprises melamine formaldehyde resin and a rubidium magnet; the hydrophilic modified thermal shrinkage fiber net is a woven net formed by hydrophilic modified polypropylene fibers and hydrophilic modified nylon fibers. The hydrophilic modified heat-shrinkable fiber net and the electromagnetic induction self-repairing microcapsule are simultaneously introduced into a UHPC concrete matrix, a synergistic effect is exerted to repair cracks, the overall performance of the concrete can be effectively improved, the toughness, crack resistance, impact resistance and the like of the obtained concrete are remarkably improved, and the service life of the concrete is prolonged. And meanwhile, on-demand release of the repairing material in the self-repairing microcapsule can be realized, the utilization efficiency of the repairing agent is improved, and the applicability is wide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and particularly relates to a self-repairing UHPC concrete and a preparation method thereof. Background Art

[0002] Ultra-high performance concrete (UHPC) is an excellent concrete material, which is usually composed of a high proportion of cement, fine aggregate and mineral admixtures (such as silica fume and fly ash), combined with chemical admixtures to enhance performance. The notable features of UHPC include high compressive strength (up to 150MPa or more), excellent durability (anti-penetration, anti-freeze and thaw, and anti-chemical erosion) and better toughness. It is suitable for use in harsh environments and is widely used in bridges, tunnels and high-strength building structures. However, it may still cause cracks due to factors such as temperature changes, plastic shrinkage, improper construction and external loads.

[0003] In order to enhance the toughness and crack resistance of ultra-high performance concrete, adding fibers is an effective method. Fibers effectively disperse stress and limit the expansion of cracks by forming a three-dimensional network structure, thereby delaying the formation of cracks. The addition of fibers not only improves the impact resistance and fatigue resistance of concrete, but also improves the reliability of its overall structure. To further enhance the self-healing ability of concrete, microcapsules can be added to the concrete. The microcapsules contain repair agents. When cracks occur in the concrete, these capsules will rupture and release the repair agents, automatically filling the cracks and promoting healing.

[0004] At present, although there have been some reports on the introduction of fiber mesh and self-healing microcapsule technology into concrete, there are still many problems and shortcomings, and it is impossible to comprehensively and effectively solve the strength, durability and self-healing of concrete structures. For example: 1) For fiber mesh technology, although it can enhance the mechanical properties of concrete to a certain extent, the use of fiber mesh alone often cannot effectively deal with the problem of crack expansion of concrete in complex environments. Moreover, with the passage of time and the continuous action of external stress, the fiber mesh may suffer fatigue damage and cannot play a long-term and stable reinforcing role; in addition, the fiber mesh has limited ability to repair larger cracks, making it difficult to achieve the self-healing function of concrete structures; 2) Heat-shrinkable fiber means usually use short-cut heat-shrinkable fibers, which can be used in cement hydration. A shrinkage response occurs during the heat release process, and prestress is applied to the concrete to improve its crack resistance, etc. However, the effect of simple heat-shrinkable fiber modification is limited and mainly works under the specific temperature conditions of the design. For actual engineering environments with a small temperature change range, its heat-shrinkage performance may not be fully utilized; in addition, the effect of chopped heat-shrinkable fibers on the durability of concrete is not obvious, and it cannot effectively solve the corrosion and aging problems that concrete has faced for a long time; 3) Microcapsule self-repairing technology, although it can achieve a certain degree of self-repairing, usually has problems such as uncontrollable release process of repair materials or limited control effect, which affects the self-repairing effect. In addition, simple self-repairing microcapsules have limited improvement on the overall mechanical properties of concrete and cannot meet some engineering requirements with higher strength requirements. Summary of the invention

[0005] The main purpose of the present invention is to provide a self-repairing UHPC concrete in view of the problems and shortcomings of the prior art. By introducing hydrophilic modified heat-shrinkable fiber mesh and electromagnetic induction self-repairing microcapsules into the UHPC concrete matrix, the high strength and toughness and excellent durability of the obtained concrete can be effectively taken into account, and at the same time, the controllable release of the repair material in the self-repairing microcapsules can be achieved, thereby improving the utilization efficiency of the repair agent and having a wide applicability.

[0006] To achieve the above object, the technical solution adopted by the present invention is:

[0007] A self-repairing UHPC concrete comprises a UHPC concrete matrix and magnetic induction self-repairing microcapsules and hydrophilic modified heat shrinkable fiber nets distributed therein, wherein the magnetic induction self-repairing microcapsules comprise a core material and a wall material, the core material adopts isophorone diisocyanate, and the wall material comprises melamine formaldehyde resin and rubidium magnet powder; the hydrophilic modified heat shrinkable fiber net is a woven net formed by hydrophilic modified polypropylene fibers and hydrophilic modified nylon fibers.

[0008] In the above scheme, the raw materials and their weight proportions include: 2270-2475 parts of UHPC concrete matrix raw materials, 34-102 parts of electromagnetic induction self-healing microcapsules, and 60-80 parts of hydrophilic modified heat shrinkable fiber mesh.

[0009] Furthermore, in the raw materials of the UHPC concrete matrix, the raw materials and their weight proportions include: 850 parts of cement, 140-160 parts of silica fume, 130-150 parts of microspheres, 600-650 parts of quartz sand, 220-260 parts of mineral powder, 140-160 parts of steel fiber, 10-15 parts of water reducer, and 180-220 parts of water.

[0010] Furthermore, the average particle size of the electromagnetic induction self-healing microcapsules is 80-125 μm, and the average thickness of the capsule wall is 8.0-12.5 μm.

[0011] Furthermore, the electromagnetic induction self-repairing microcapsules account for 4-12% of the cement mass.

[0012] Furthermore, the preparation method of the electromagnetic induction self-repairing microcapsule comprises the following steps:

[0013] 1) mechanically stirring an isophorone diisocyanate (IPDI) and polystyrene maleic anhydride copolymer (SMA) emulsifier solution;

[0014] 2) dissolving a portion of the melamine formaldehyde resin in an aqueous solution of polyvinyl alcohol to obtain a melamine formaldehyde resin solution, and adding the melamine formaldehyde resin solution to the solution system obtained in step 1) to carry out a cross-linking reaction to obtain a prepolymer solution of the melamine formaldehyde resin;

[0015] 3) adding rubidium magnet powder to the dispersant solution (aqueous solution), then adding the remaining melamine formaldehyde resin, mixing evenly, adding the obtained dispersion to the reaction product obtained in step 2), heating and stirring, to obtain a suspension of electromagnetic induction microcapsules;

[0016] 4) Centrifugally separating the obtained microcapsules, performing curing treatment, and drying to obtain the electromagnetic induction self-healing microcapsules.

[0017] In the above scheme, the mass ratio of the introduced melamine formaldehyde resin, isophorone diisocyanate and rubidium magnet powder is (5-9):(10-18):(4-8).

[0018] In the above scheme, the mechanical stirring rate of step 1) is 300-500 r / min, and the time is 1-2 h.

[0019] In the above scheme, the emulsifier solution is prepared by adjusting the pH value of the emulsifier (using NaOH) to 10-12, and then adding water and stirring to dissolve the emulsifier to a concentration of 2-4 wt%.

[0020] In the above scheme, the mass ratio of isophorone diisocyanate to polystyrene maleic anhydride copolymer is 10:(3-7).

[0021] In the above scheme, in the melamine formaldehyde resin solution in step 2), the concentration of melamine formaldehyde resin is 5-15wt%; the concentration of polyvinyl alcohol is 6-10%.

[0022] In the above scheme, the amount of melamine formaldehyde resin used in step 2) accounts for 50-60% of the mass of the core material IPDI.

[0023] In the above scheme, the temperature of the cross-linking reaction stirring treatment is 45-50° C., the time is 0.5-1 h, and the mechanical stirring rate is 400-550 r / min.

[0024] In the above scheme, the dispersant can be selected from one or more of sodium dodecyl sulfate, oleic acid, polyethylene glycol, etc.

[0025] In the above scheme, in the dispersion obtained in step 3), the concentration of the neodymium magnet powder is 15-20wt%, the concentration of the melamine formaldehyde resin is 60-70wt%, and the concentration of the dispersant is 19-25wt%.

[0026] In the above scheme, the temperature used for the heating and stirring treatment is 75-80°C and the time is 1.5-2.5h.

[0027] In the above scheme, the curing treatment step includes: adding oxalic acid solution to melamine formaldehyde resin solution (same as the preparation method described in step 2), stirring evenly to obtain a curing liquid; adding microcapsules obtained by centrifugation to the curing liquid, stirring evenly, and performing a curing reaction at a temperature of 50 to 100° C. for 1 to 5 hours; taking out the microcapsules, washing them with an organic solvent (such as ethanol or acetone), and drying (40 to 60° C., 2 to 8 hours) to obtain cured magnetic induction self-healing microcapsules.

[0028] Furthermore, the melamine formaldehyde resin solution is the same as the melamine formaldehyde resin solution obtained in step 2).

[0029] In the above scheme, the concentration of the oxalic acid solution is 1-5%.

[0030] In the above scheme, the volume ratio of the oxalic acid solution to the melamine formaldehyde resin solution is 1:(2.5-7).

[0031] In the above scheme, the hydrophilically modified heat shrinkable fiber mesh is made of hydrophilically modified polypropylene fibers and hydrophilically modified nylon fibers by using a double twisted weaving process.

[0032] Furthermore, the hydrophilic modified heat shrinkable fiber mesh has a melting point of 150-220° C. and shrinks at 120-180° C.

[0033] In the above scheme, the pore size of the hydrophilic modified heat shrinkable fiber mesh is 20 to 30 mm.

[0034] In the above scheme, the thermal shrinkage starting temperature of the polypropylene fiber is 120-140°C, and its molecular weight is 100,000-300,000; the thermal shrinkage starting temperature of the nylon fiber is 140-180°C, and its molecular weight is 20,000-70,000; the diameters of the polypropylene fiber and the nylon fiber are 10-50 μm.

[0035] In the above scheme, the hydrophilic modification step is to sequentially coat methyl ethyl cellulose and graft modification with acrylic acid, and the specific steps include:

[0036] 1) adding polypropylene fiber or nylon fiber to ethanol for soaking treatment to obtain pretreated fiber (pretreated polypropylene fiber or pretreated nylon fiber);

[0037] 2) adding the pretreated fiber into an ethanol solution of methyl ethyl cellulose, soaking it at 40-60° C. for 2-4 hours, and washing it to obtain a methyl ethyl cellulose coated modified fiber;

[0038] 3) The obtained methyl ethyl cellulose coated modified fiber is placed in an acrylic acid solution, and grafted at 60-80° C. for 4-6 hours. The fiber is taken out, washed with water, and dried to obtain a hydrophilically modified polypropylene fiber or nylon fiber.

[0039] In the above scheme, the soaking treatment time in step 1) is 2 to 3 hours.

[0040] In the above scheme, the concentration of methylethyl cellulose in the ethanol solution of methylethyl cellulose is 5 to 10 g / mL.

[0041] In the above scheme, the introduced methyl ethyl cellulose accounts for 3-8% of the mass of the pretreated fiber.

[0042] In the above scheme, the acrylic acid introduced in step 3) accounts for 5-15% of the mass of the pretreated fiber.

[0043] In the above scheme, the concentration of the acrylic acid solution is 10 to 30 wt%.

[0044] In the above scheme, in the blended low-melting-point heat-shrinkable fiber web, the blending ratio (mass ratio) of the hydrophilically modified polypropylene fiber and the hydrophilically modified nylon fiber is 1:2 to 2:1.

[0045] Preferably, the blended low-melting-point heat-shrinkable fiber mesh is woven by a double-twisted weaving process and then further subjected to an indentation treatment to increase the mechanical bite force between the fiber mesh and the concrete matrix.

[0046] Furthermore, the silicate cement is PO52.5, PO62.5 ordinary silicate cement or P·I type silicate cement.

[0047] Furthermore, the quartz sand has a particle size of 26 to 70 meshes.

[0048] Furthermore, the mineral powder is of S95 grade or above.

[0049] In the above scheme, the specific surface area of ​​the silica fume is 13 to 30 m 2 / g, activity index 85-120%; average microbead size 0.5-10μm, density 2.2-2.4g / cm 3 .

[0050] Furthermore, the water reducing agent is a polycarboxylic acid water reducing agent, and the water reducing rate is >30%.

[0051] In the above scheme, the steel fiber is a copper-plated short steel fiber with a density of 80-160 kg / m 3 , its nominal length is 12~17mm, and its equivalent diameter is 0.15~0.30mm.

[0052] The above-mentioned method for preparing a self-repairing UHPC concrete comprises the following steps:

[0053] 1) 850 parts of cement, 140-160 parts of silica fume, 130-150 parts of microspheres, 600-650 parts of quartz sand, 220-260 parts of mineral powder, 140-160 parts of steel fiber and 3-6 parts of admixture are mixed evenly, and then 180-220 parts of water and 10-15 parts of water reducing agent are added and mixed evenly to obtain UHPC concrete matrix slurry;

[0054] 2) placing the hydrophilic modified heat shrinkable fiber mesh in the middle of the mold;

[0055] 3) Add 34 to 102 parts of electromagnetic induction self-repairing microcapsules to the UHPC concrete matrix slurry and stir evenly, then pour into a mold provided with a hydrophilic modified heat shrinkable fiber mesh, shape, and cure to obtain the self-repairing UHPC concrete.

[0056] In the above solution, the anti-UHPC concrete is a cylindrical or block structure.

[0057] Furthermore, when preparing cylindrical UHPC concrete, the blended low-melting point heat-shrinkable fiber mesh is in a hollow cylindrical shape and is arranged in a middle position coaxial with the cylindrical UHPC concrete; when preparing block UHPC concrete, the blended low-melting point heat-shrinkable fiber mesh is in a planar mesh structure and is arranged in the middle position of the cylindrical UHPC concrete along the thickness direction parallel to the surface of the UHPC concrete.

[0058] Furthermore, when preparing cylindrical UHPC concrete, in the pouring process of step 3), the mixture is first poured into the hollow cylindrical blended low-melting point heat-shrinkable fiber mesh, and after hardening and shaping, the remaining mixture is continued to be poured until the mold is filled.

[0059] In the above scheme, the UHPC concrete adopts a standard curing process.

[0060] The self-repairing UHPC concrete prepared according to the above scheme has a compressive strength of 183.7 to 263.4 MPa, an impact and abrasion resistance of 170.5 to 231.3 MPa, and a toughness of 2103.1 to 10826 J.

[0061] The principle of the present invention is:

[0062] The invention uses polypropylene fiber and nylon fiber with heat shrink effect as main raw materials to prepare heat shrinkable fiber net. Firstly, polypropylene fiber and nylon fiber are respectively coated with methyl ethyl cellulose and modified by acrylic acid grafting in sequence, which can effectively reduce the crystallinity of the fiber, and form a blended low-melting-point heat shrinkable fiber with low crystallinity and high orientation characteristics, which is beneficial to improve the heat shrinkage rate of the obtained fiber net; in addition, the surface of the modified fiber is hydrophilic, so that the fiber is more easily wrapped and bonded by cement slurry, which is beneficial to enhance the bonding effect between the fiber and the concrete matrix.

[0063] The electromagnetic induction self-healing microcapsules of the present invention can release the core material on demand and improve the utilization efficiency of the repair agent: first, the emulsifier SMA and IPDI are used for mechanical stirring to form a stable emulsified system, and then MF and PVA are introduced to carry out a cross-linking reaction under suitable temperature and stirring conditions to optimize the cross-linking density of the wall material, and preliminarily construct a relatively stable wall material basic structure to provide a relatively stable framework structure for the subsequent further coating of the magnetocaloric particles, and then the heating and stirring conditions of the MF and the magnetocaloric particles are adjusted to promote the magnetocaloric particles to be stably coated inside the microcapsules, thereby ensuring a good magnetocaloric controlled release effect.

[0064] The present invention combines the heat-shrinkable fiber reinforcement technology with the electromagnetic controlled-release microcapsule self-repairing technology, and jointly incorporates the hydrophilic modified heat-shrinkable fiber mesh and the electromagnetic induction self-repairing microcapsules into UHPC concrete. The introduced heat-shrinkable fiber mesh can form a continuous network structure in the entire cement-based material, provide global reinforcement, and significantly improve the overall performance of the concrete; the heat release of cement hydration causes the heat-shrinkable fiber mesh to shrink in response (one-time shrinkage provides stress resistance and crack resistance), and the pre-compression stress generated on the surrounding hardened gel slurry can effectively inhibit the formation or expansion of microcracks. By dispersing these stresses, the microcracks can exhibit better ductility and impact resistance when subjected to impact or vibration, thereby preventing brittle damage; the introduced electromagnetic induction self-repairing microcapsules can controllably release the inner core repair agent under the action of an external magnetic field, effectively repairing the cracks, and the heat released at the same time will cause the fiber mesh to shrink twice, synchronously applying extrusion stress to the cracks, and synergistically improving the crack repair effect.

[0065] Compared with the prior art, the present invention has the following beneficial effects:

[0066] 1) Blended low melting point heat shrinkable fiber mesh

[0067] The present invention uses polypropylene fiber and nylon fiber with heat shrinkage effect as main raw materials to prepare heat shrinkable fiber mesh. Firstly, polypropylene fiber and nylon fiber are respectively coated with methyl ethyl cellulose and modified by propionic acid grafting in sequence, which can effectively reduce the crystallinity of the fiber and improve its orientation and surface hydrophilicity, which is beneficial to improve the heat shrinkage performance of the obtained fiber mesh and enhance the bonding effect between the fiber and the concrete matrix, thereby promoting the improvement of the toughness, crack resistance and impact resistance of the concrete.

[0068] 2) Electromagnetic induction microcapsules;

[0069] The present invention uses melamine formaldehyde resin with high mechanical strength and chemical stability and good compatibility with concrete as the main capsule wall material, and combines rubidium magnetic powder to give the microcapsule a strong magnetic response, which can effectively improve the controlled release performance; the introduced core material IPDI can react with water after release, effectively enhancing the durability of concrete; the obtained microcapsule can release the core material as needed, thereby improving the utilization efficiency of the repair agent;

[0070] 3) The present invention combines the hydrophilic modified heat-shrinkable fiber mesh with the electromagnetic induction self-healing microcapsule method, and applies them together to the UHPC concrete system. The heat release of cement hydration causes the heat-shrinkable fiber mesh to shrink in response, and generates pre-compression stress on the surrounding hardened gel slurry, thereby improving the crack resistance of the concrete. Under the action of an external magnetic field, the capsule wall of the electromagnetic induction self-healing microcapsule ruptures, and the repair agent flows into the crack. At the same time, the heat-shrinkable fiber mesh is stimulated to shrink in response to heat, and an extrusion force is simultaneously applied to the crack. The two work together to repair the crack, which can effectively maintain the high precision (dimensional accuracy, shape accuracy, performance accuracy, etc.) and high durability of UHPC, especially for resisting long-term environmental erosion and internal stress changes of the structure. In addition, the strengthening and toughening effect of the heat-shrinkable fiber mesh plays a key role when UHPC is subjected to a large one-time load, and the self-healing function of the electromagnetic controlled-release capsule plays an intermittent role as microcracks gradually occur during the long-term use of the UHPC structure. The two complement each other and provide comprehensive performance guarantee for UHPC concrete. BRIEF DESCRIPTION OF THE DRAWINGS

[0071] Figure 1 This is a schematic diagram of the structure of the UHPC concrete according to an embodiment of the present invention;

[0072] Figure 2 Comparison of the self-repairing effects of UHPC concrete cracks that are simultaneously incorporated with heat-shrinkable fiber mesh and electromagnetic induction microcapsules: (a) before repair; (b) after repair. DETAILED DESCRIPTION

[0073] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.

[0074] In the following embodiments, the hydrophilically modified heat shrinkable fiber mesh is woven by using hydrophilically modified polypropylene fibers and hydrophilically modified nylon fibers through a double twisted weaving process.

[0075] The mechanical and physical property test results of the polypropylene fiber and nylon fiber used are shown in Table 1 and Table 2, respectively; the pore size parameter characteristics of the obtained blended low-melting point fiber mesh are shown in Table 3.

[0076] Table 1 Mechanical and physical properties of polypropylene fibers

[0077]

[0078] Table 2 Mechanical and physical properties of nylon fibers

[0079]

[0080] The preparation method of the hydrophilic modified heat shrinkable fiber mesh comprises the following steps:

[0081] 1) placing polypropylene fiber or nylon fiber into a reactor, adding ethanol that can completely immerse the fiber, and soaking for 2 hours to remove impurities and oil stains on the fiber surface, thereby obtaining pretreated polypropylene fiber or nylon fiber;

[0082] 2) adding methyl ethyl cellulose to ethanol at a ratio of 5 g of methyl ethyl cellulose to every 100 ml of ethanol, stirring evenly, and preparing an ethanol solution of methyl ethyl cellulose (the concentration of methyl ethyl cellulose is 5 g / mL); taking out the pretreated fiber, putting it into the prepared ethanol solution of methyl ethyl cellulose (the introduced methyl ethyl cellulose accounts for 4% of the mass of the pretreated fiber), and soaking it at 40° C. for 2 h to obtain methyl ethyl cellulose coated modified fiber; taking out the fiber, rinsing it with deionized water, and removing the residual solution on the surface;

[0083] 3) placing the washed fiber into an acrylic acid solution (concentration of 20 wt%), wherein the amount of introduced acrylic acid is 5% of the fiber mass, and performing a grafting reaction at 60° C. for 4 h;

[0084] 4) After the reaction is completed, the fiber is taken out and repeatedly rinsed with deionized water to remove unreacted monomers and impurities, and then the fiber is dried for 10 hours to obtain a hydrophilically modified heat-shrinkable fiber;

[0085] 6) The hydrophilically modified polypropylene fiber and nylon fiber are blended (the blending ratio is 1:2 or 2:1) and woven into a grid shape by using a double twisted weaving process.

[0086] Table 3 Characteristics of pore size parameters of hydrophilic modified heat shrinkable fiber mesh

[0087]

[0088] The method for preparing the electromagnetic induction self-repairing microcapsules comprises the following steps:

[0089] 1) 10 g of isophorone diisocyanate IPDI and 150 mL of polystyrene maleic anhydride copolymer SMA emulsifier solution (the emulsifier SMA is hydrolyzed by adding NaOH to adjust the pH to 10, and then stirring and dissolving to obtain a 2 wt% SMA emulsifier solution) are mechanically stirred for 2 h at a speed of 400 r / min;

[0090] 2) 5 g of melamine formaldehyde resin MF and 50 mL of polyvinyl alcohol solution (the mass ratio of PVA to water is 1:10) are mixed evenly to obtain a melamine formaldehyde resin solution, which is then added to the solution obtained in step 1) to carry out a cross-linking reaction at 50° C. for 1 h with a mechanical stirring rate of 550 r / min;

[0091] 3) Add 2 g of melamine formaldehyde resin MF and 50 mL of rubidium magnet dispersion (the dispersant used is sodium dodecyl sulfate, in which the amount of rubidium magnet is 4 g and the amount of dispersant is 1.41 g) and heat and stir at 80° C. for 2 h;

[0092] 4) filtering the above electromagnetic controlled release microcapsule suspension, washing the microcapsules with 75% ethanol by mass, and filtering again after washing to obtain relatively pure microcapsules; slowly adding 3% oxalic acid solution by mass to the melamine formaldehyde resin solution (the melamine formaldehyde resin solution obtained in step 2), wherein the volume ratio of the oxalic acid solution to the melamine formaldehyde resin solution is 1:2.5, stirring evenly, and obtaining a solidified liquid; adding the pretreated microcapsules to the solidified liquid, stirring evenly, and curing the mixed solution at 60° C. for 3 hours;

[0093] 5) After the curing reaction is completed, the microcapsules are taken out from the curing liquid and washed with 75% by mass ethanol to remove the curing liquid and impurities remaining on the surface; the obtained microcapsules are dried at 60° C. for 8 hours to finally obtain cured electromagnetic controlled release microcapsules.

[0094] Table 4 Performance test results of electromagnetic controlled release microcapsules

[0095]

[0096]

[0097] In the following examples, the silicate cement used is PO52.5, and the specific surface area of ​​silica fume is 136364cm 2 / g, activity index is 120%, average size of micro beads is 0.5μm, particle size of quartz sand is 42 mesh, mineral powder is S95 grade, steel fiber is copper-plated short steel fiber, density is 80kg / m 3 , nominal length is 12-17mm, equivalent diameter is 0.15-0.30mm, the water reducer is polycarboxylic acid water reducer, and the water reduction rate is 35%.

[0098] Example 1

[0099] A self-repairing UHPC concrete, the preparation method of which comprises the following steps:

[0100] 1) 850 parts of cement, 150 parts of silica fume, 150 parts of microspheres, 600 parts of quartz sand, 240 parts of mineral powder, 150 parts of steel fiber and 34 parts of electromagnetic induction self-repairing microcapsules were mixed evenly, and then 200 parts of water and 10 parts of water reducer were added and mixed evenly, and stirred for 2 minutes to obtain UHPC concrete slurry;

[0101] 2) Place 60 parts of a hydrophilic modified heat shrinkable fiber mesh (the blending ratio of hydrophilic modified polypropylene fiber to nylon fiber is 1:2) in a mold with a cylindrical cavity, first fill part of the UHPC concrete slurry into the cylindrical fiber mesh, and then continue to fill the entire mold after the concrete inside is set;

[0102] 3) Curing after forming to obtain the self-repairing UHPC concrete.

[0103] Comparative Example 1

[0104] A conventional UHPC concrete, the preparation method of which comprises the following steps:

[0105] 1) 850 parts of cement, 850 parts of cement, 150 parts of silica fume, 150 parts of microspheres, 600 parts of quartz sand, 240 parts of mineral powder and 150 parts of steel fiber were mixed evenly, and then 200 parts of water and 10 parts of water reducing agent were added and mixed evenly to obtain UHPC concrete slurry;

[0106] 2) The obtained UHPC concrete slurry is poured and cured to obtain a UHPC concrete specimen.

[0107] Comparative Example 2

[0108] A hydrophilic modified heat shrinkable fiber mesh reinforced concrete, the preparation method of which comprises the following steps:

[0109] 1) Mixing of concrete slurry: 850 parts of cement, 150 parts of silica fume, 150 parts of microspheres, 600 parts of quartz sand, 240 parts of mineral powder and 150 parts of steel fiber are mixed evenly, and then 200 parts of water and 10 parts of water reducing agent are added and mixed evenly to obtain concrete slurry;

[0110] 2) 60 parts of a hydrophilically modified heat-shrinkable fiber mesh (the blending ratio of the hydrophilically modified polypropylene fiber and the nylon fiber is 1:2, and the preparation method is the same as in Example 1) are placed in a mold with a cylindrical cavity, and first a portion of the UHPC concrete slurry is filled into the cylindrical fiber mesh, and then the entire mold is filled after the concrete inside is formed; after forming, curing is performed to obtain hydrophilically modified heat-shrinkable fiber mesh reinforced concrete.

[0111] Comparative Example 3

[0112] A UHPC concrete based on electromagnetic induction self-repairing microcapsules, the preparation method of which comprises the following steps:

[0113] 1) 850 parts of cement, 150 parts of silica fume, 150 parts of microspheres, 600 parts of quartz sand, 240 parts of mineral powder, 150 parts of steel fiber and 34 parts of electromagnetic induction self-repairing microcapsules (preparation method is the same as in Example 1) were mixed evenly, and then 200 parts of water and 10 parts of water reducing agent were added and mixed evenly, and stirred for 2 minutes to obtain concrete slurry;

[0114] 2) pouring and curing the concrete slurry to obtain UHPC concrete based on electromagnetic induction microcapsules.

[0115] Comparative Example 4

[0116] A UHPC concrete based on hydrophilic modified chopped fibers and electromagnetic induction self-repairing microcapsules, the preparation method of which comprises the following steps:

[0117] 1) Mixing of concrete slurry: 850 parts of cement, 150 parts of silica fume, 150 parts of microspheres, 600 parts of quartz sand, 240 parts of mineral powder, 150 parts of steel fiber, 60 parts of hydrophilically modified polypropylene, hydrophilically modified short fibers (including 20 parts of hydrophilically modified polypropylene and 40 parts of hydrophilically modified nylon short fibers), and 34 parts of electromagnetic induction self-repairing microcapsules (preparation method is the same as in Example 1) are mixed evenly, and then 200 parts of water and 10 parts of water reducing agent are added and mixed evenly to obtain concrete slurry; wherein, the hydrophilic modification steps of hydrophilically modified polypropylene and nylon short fibers are the same as in Example 1; the average length of hydrophilically modified polypropylene is 12 mm; the average length of hydrophilically modified nylon short fibers is 16 mm;

[0118] 3) The obtained concrete slurry is poured, and after forming, it is cured to obtain UHPC concrete reinforced with hydrophilic modified chopped fibers and electromagnetic induction microcapsules.

[0119] Comparative Example 5

[0120] A UHPC concrete based on a heat-shrinkable fiber mesh and electromagnetic induction self-repairing microcapsules, wherein the preparation method thereof comprises the following steps:

[0121] 1) 850 parts of cement, 150 parts of silica fume, 150 parts of microspheres, 600 parts of quartz sand, 240 parts of mineral powder, 150 parts of steel fiber and 34 parts of electromagnetic induction self-repairing microcapsules (preparation method is the same as in Example 1) were mixed evenly, and then 200 parts of water and 10 parts of water reducer were added and mixed evenly, and stirred for 2 minutes to obtain UHPC concrete slurry;

[0122] 2) 60 portions of the heat-shrinkable fiber mesh are placed in a mold having a cylindrical cavity, and a portion of the UHPC concrete slurry is first filled into the cylindrical fiber mesh, and then the entire mold is filled after the concrete inside is formed; wherein the preparation method of the heat-shrinkable fiber mesh is substantially the same as that of Example 1, except that the hydrophilic modification is not performed before the blended weaving;

[0123] 3) Curing after forming to obtain the self-repairing UHPC concrete.

[0124] The concrete obtained in Example 1 and Comparative Examples 1 to 5 were tested for mechanical properties and durability, and the results are shown in Table 4.

[0125] Table 4 Performance test results of concrete obtained in Example 1 and Comparative Examples 1 to 5 after curing for 28 days

[0126]

[0127]

[0128] In Table 4, the toughness improvement rate is the improvement rate relative to Comparative Example 1.

[0129] A self-healing experiment was conducted on the self-repairing UHPC concrete obtained in Example 1, and the specific steps included:

[0130] Using the splitting test method, micro cracks of 0.15 to 0.30 mm were produced on the surface of the specimen. The specimen was immediately removed and the initial crack width was measured.

[0131] For the above concrete specimens, the temperature was raised to 340℃ and the crack repair was further observed under the condition of magnetic field strength of 0.3T. The specific repair results are shown in Figure 2 It can be seen that the concrete of the present invention can achieve self-repair of cracks with a width of 0.30 mm under a 300 mT magnetic field.

[0132] Further experiments showed that as the magnetic field intensity increases, the amount of repair material (core material) released from the microcapsule increases, with less release at low magnetic field intensity and effective crack repair at high magnetic field intensity; different magnetic field frequencies lead to different release rates and patterns, low-frequency slow release is suitable for long-term repair, and high-frequency fast release is used for emergency treatment.

[0133] Example 2

[0134] A self-repairing UHPC concrete (the specimen is in block shape), wherein the components and their weight proportions include: 2053 parts of self-repairing UHPC concrete raw materials; wherein the self-repairing UHPC concrete raw materials include: 850 parts of cement, 150 parts of silica fume, 150 parts of microspheres, 600 parts of quartz sand, 240 parts of mineral powder, 150 parts of steel fiber, 200 parts of water, and 10 parts of water reducer; wherein the hydrophilic modified heat shrinkable fiber net is obtained by using a double twisting process to blend hydrophilic modified polypropylene fiber and nylon fiber according to different blending ratios (see Table 5); the preparation method of the self-repairing UHPC concrete includes the following steps:

[0135] 1) 850 parts of cement, 150 parts of silica fume, 150 parts of microspheres, 600 parts of quartz sand, 240 parts of mineral powder, 150 parts of steel fiber, and 3 parts of admixture were mixed with different amounts (mass percentage of cement dosage) of electromagnetic induction self-repairing microcapsules (see Table 5 for details), and then 200 parts of water and 10 parts of water reducer were added and mixed evenly, and stirred for 2 minutes to obtain UHPC concrete slurry;

[0136] 2) 60 portions of the hydrophilic modified heat shrinkable fiber mesh were placed in the middle of the mold and the impact-resistant concrete slurry was poured to fill the entire mold. After molding, the mold was placed in a curing room for 28 days (temperature 25° C., humidity 95%) to obtain self-repairing UHPC concrete.

[0137] Table 5 Performance test results of different fiber mesh-electromagnetic controlled release capsule systems and the obtained concrete used in Example 2

[0138]

[0139]

[0140] The above embodiments are merely examples for clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.

Claims

1. A self-repairing UHPC concrete, characterized in that: It includes a UHPC concrete matrix and magnetic induction self-repairing microcapsules and hydrophilic modified heat shrinkable fiber mesh distributed therein; the magnetic induction self-repairing microcapsules include core materials and wall materials, the core material is made of isophorone diisocyanate, and the wall material includes melamine formaldehyde resin and rubidium magnet powder; the hydrophilic modified heat shrinkable fiber mesh is a woven mesh formed by hydrophilic modified polypropylene fibers and hydrophilic modified nylon fibers.

2. The self-repairing UHPC concrete according to claim 1, characterized in that: The raw materials and their weight proportions include: 2270-2475 parts of UHPC concrete matrix raw materials, 34-102 parts of electromagnetic induction self-repairing microcapsules, and 60-80 parts of hydrophilic modified heat shrinkable fiber mesh.

3. The self-repairing UHPC concrete according to claim 1, characterized in that: The raw materials of the UHPC concrete matrix include: 850 parts of cement, 140-160 parts of silica fume, 130-150 parts of microspheres, 600-650 parts of quartz sand, 220-260 parts of mineral powder, 140-160 parts of steel fiber, 10-15 parts of water reducer, and 180-220 parts of water.

4. The self-repairing UHPC concrete according to claim 1, characterized in that: The mass ratio of melamine formaldehyde resin, isophorone diisocyanate and rubidium magnet powder introduced into the electromagnetic induction self-repairing microcapsule is (5-9):(10-18):(4-8).

5. The self-repairing UHPC concrete according to claim 1, characterized in that: The heat shrinkage starting temperature of the polypropylene fiber is 120-140° C.; the heat shrinkage starting temperature of the nylon fiber is 140-180° C.; the diameters of the polypropylene fiber and the nylon fiber are 10-50 μm.

6. The self-repairing UHPC concrete according to claim 1, characterized in that: The hydrophilic modification step is to sequentially coat methyl ethyl cellulose and graft modification with acrylic acid.

7. The self-repairing UHPC concrete according to claim 1, characterized in that: In the hydrophilically modified heat shrinkable fiber net, the blending ratio of the hydrophilically modified polypropylene fiber and the hydrophilically modified nylon fiber is 1:2 to 2:

1.

8. The self-repairing UHPC concrete according to claim 1, characterized in that: The silicate cement is PO52.5, PO62.5 ordinary silicate cement or P·I type silicate cement; the quartz sand particle size is 26-70 mesh; the mineral powder is S95 grade or above; the steel fiber is copper-plated short steel fiber 80-160kg / m 3 , its nominal length is 12~17mm, and its equivalent diameter is 0.15~0.30mm.

9. The self-repairing UHPC concrete according to claim 1, characterized in that: The water reducing agent is a polycarboxylic acid water reducing agent, and the water reducing rate is >30%.

10. The method for preparing the self-repairing UHPC concrete according to any one of claims 1 to 9, characterized in that: The following steps are involved: 1) Prepare UHPC concrete matrix slurry; 2) placing the hydrophilic modified heat shrinkable fiber mesh in the middle of the mold; 3) adding the electromagnetic induction microcapsules to the UHPC concrete matrix slurry and stirring them evenly, then pouring them into a mold provided with a hydrophilic modified heat shrinkable fiber mesh, molding, and curing to obtain the self-repairing UHPC concrete.

Citation Information

Patent Citations

  • Electromagnetic induction cement concrete crack self-repair diisocyanate microcapsule and preparation method thereof

    CN108483964A

  • UHPC bathroom product and preparation method thereof

    CN110078434A

  • Electromagnetic controlled-release microcapsule / steel fiber self-repairing concrete and preparation method thereof

    CN111393063A

  • Blend fiber and nested microcapsule self-repairing concrete and preparation method thereof

    CN118724525A

  • Synthetic short fiber composition and self-repairing type concrete

    JP2014076913A

Cited By

  • Functional composite capsule servo fiber for concrete and preparation method

    CN120208573A